Palm Functional Traits, Soil Fertility and Hydrology Relationships in Western Amazonia - Trujillo, William; Rivera-Rondón, Carlos A.; Balslev, Henrik (Frontiers in Forests and Global Change, 2021)
Quantification of multivariate trait spectra (or axes of specialization) make the definition of plant strategies more operational, which promotes trait-based theory of community assembly and the understanding of dynamics and functioning of ecosystems. We used field-quantified soil data to explore trait-environment relationships across palm communities in western Amazonia. We collected data from 116 palm species in 458 transects across four distinct forest types. We combined these data with trait records to relate local plant community trait composition to broad gradients in soil variables and forest types. There were significant trait-environment relationships across western Amazonia. Palms with large leaves and fruits, and palms with both growth forms (acaulescent/erect) were associated with fertile soils, while palms with unarmed leaves and stems were associated with non-inundated environments. These results suggest that the functional traits of palms vary consistently along soil gradients on a regional scale. This variation could be explained by the soil fertility and acidity + aluminum gradients, suggesting environmental filters related to resource availability and stressful environments, such as acid soils and soils with high aluminum content.